PERHITUNGAN HARGA OPSI EROPADENGAN METODE TRINOMIAL PADA PERUSAHAAN MITSUBISHI - Paiz Jalaludin; Alrafiful Rahman; Ani Nuraini; Royyan Amigo (POLITEKNIK LP3I JAKARTA, 2024)
Investment is an important instrument in the financial market. The investment objective is to obtain large profits with minimum capital. The trend that is currently developing is that investors are not only interested in investing in real assets, but they have great attention to investing in financial assets such as shares. However, to gain profits, investors must face risk and uncertainty. Among the solutions to reduce these risks are derivatives. Stock options are one of the widely used derivative products. An important instrument in stock options is the method of determining option prices according to the type of option. European option prices can be determined using several methods, namely the Black-Scholes method, binomial method, and trinomial method. This research aims to implement the trinomial method in determining European option prices, both Call options and Put options on Mitsubishi UFJ Financial Group (MUFG) shares. The results of determining option prices using the trinomial method are then compared with the results of the Black-Scholes method which aims to analyze the convergence of the two. The research results show that the trinomial method can be used to determine stock option prices for the Mitsubishi company more flexibly than the Black-Scholes method. In addition, the results show that the trinomial model converges to the Black-Scholes method.